Effect of dolomite on the thermokinetics of Biomass Pyrolysis - Razi Ahmad; Ye Lwin; Mohd Noor Ahmad, Prof. Dr.; Saiful Azhar Saad; Khudzir Ismail (Gadjah Mada University, 2008)
Organized by Gadjah Mada University, 4th - 5th December 2007 at Yogyakarta, Indonesia.